A Fast and Efficient Design Method for Circuit Analog Absorbers Consisting of Resistive Square-Loop Arrays - Ye Han; Wenquan Che; Christopoulos, Christos; Ying Xiong; Yumei Chang (IEEE transactions on electromagnetic compatibility, 2016)
This paper proposes a novel optimization design method for circuit analog absorbers consisting of resistor-loaded square-loop arrays. First, new precise equivalent circuit models (ECMs) for square-loop-array-based absorbers are derived through the synthetic asymptote method. The presented models are applicable for multilayered absorber with printed single or double SLAs on each layer. Then, the combination of this ECM and conventional genetic algorithm (GA) is proposed and provided a fast and efficient way to design broadband and low-profile SLA absorbers. For demonstration, four absorbers are designed and optimized. Finally, the agreement between the simulated and measured reflection coefficients indicates the validity of the presented method.